Bird Flu consultation. The research community's response to Avian Influenza, with special reference to the needs of developing countries - International Livestock Research Institute (International Livestock Research Institute, 2006)
The CD starts with introduction by ILRI Director General Carlos Sere Then follows the seven interviews conducted by Brian Perry, ILRI Epidemiologist covering aspects and issues of the current Avian Flu situation, their experiences, national and regional surveillance as well as community surveillance and action. The representatives were from South East Asia (Robyn Alders, IRPC/KYEEMA Foundation; India (Santanu Bandopadhyay, Ministry of Agriculture; Nigeria (Daniel F Adene, Poultry Diseases Unit, Department of Veterinary Medicine, University of Ibadan; Senegal (Poultry specialist E. Fallou Gueye ISRA/Family Poultry Network; Kenya (Catherine Wanjohi from Department of Veterinary Services); World Bank Adam lagerstedt; and South Africa (Celia Abolnik Ondeistepoort Veterinary Institute, Pretoria). The South East Asia representative talked about Laos, East Tumor. She states that Laos is one of the first countries to suffer the Bird Flu outbreak, which was in 2004. That it has small commercial industry and that people preferred village poultry. The outbreak was limited to commercial units, and that it was under control. The government's key efforts were also discussed. She indicated that in Laos no veterinarians are trained. There is luck of sufficient information and communication. Laos is still building capacity. Surveillance is one of the failures because of neglected veterinary services and education on basic sciences over many years. Community action was also discussed. The interview with India's representative started with geographical distribution of Bird Flu, and limitation to specific areas. It was indicated that it was a sudden outbreak in a district in a remote area commercial farm. Soon after, there was another outbreak in rural backyard poultries. The discussion included developing of national policies, and whom it involved. Other topics were - active laboratories, vaccination, strains imported, compensation to farmers on destroyed birds, depopulation, animal welfare, public health issues, mortalities, and community awareness. The third interviewee from Nigeria discusses cases of Bird Flu, mortality rate, diagnosis, outbreaks, training, lack of participation in surveillance, spreading mechanism, and recommendations. The representative from Senegal discusses the vulnerability of Avian Flu, preparedness, expertise, how avian flu affects the livelihood of the small farmers, risk of smuggled carcasses, role of migratory birds and water, compensation to farmers, education, training, and action. With the Kenyan representative the discussion was on role in preparedness, coordinating of activities, how effective was the surveillance system, capacity building in lab level, diagnosis methods, and bodies involved in the surveillance like the national museum which was involved in wild bird surveillance by collecting samples. He also stated that there is an active surveillance team for domestic poultry and birds, major risks are said to be migratory birds, and illegal importation. The discussion ends with what actions to be taken and control policies. The World Banks interview includes how word bank view the whole process including money and responsibility that it is not the lead agency internationally. WHO deals with the human side and FAO the other side. He stated that World Bank basically coordinates financial flow and donors & funding agencies. He mentioned that country strategy is used to allocate money and that reprogramming of funding is already in use. The discussion on South Africa is on the ongoing work which involved diagnosis and research in Avian Influenza. The discussion includes tracing the origin, mutation, strains in South Africa, Ostrich viruses, intensive farming system, identify how the virus come to the country, the surveillance program, lessons learnt, direct and indirect impact, increasing awareness, inadequate compensation, and coordination of surveillance. A summary of possible ways forward was presented by Tom Randolph, Agricultural economist at ILRI. He looked into how to develop policies to control Avian Flu, service needed to support different front line agencies, and indicates the research community can contribute by its expertise, lab capacity etc. and how to develop control policies, why and how can the community translate those lessons into better control efforts in the future. Front line agencies like, FOA, OIE and WHO and national institutes were reminded to prepare for and fight any outbreaks of the disease. It was mentioned that ILRI and IFPRI representing the CGIAR, would like to help to facilitate the process, help to get it started but not control or lead.